Generation of HNO and HSNO from nitrite by heme-iron-catalyzed metabolism with H2S - Miljkovic, Jan; Kenkel, Isabell; Ivanovic-Burmazovic, Ivana; Filipovic, Milos (Angewandte Chemie International Edition, 2013)
Taking NO for an answer: A mechanistic study has shown that a heme-iron-catalyzed pathway (see scheme) could lead to the nitrite-/sulfide- induced formation of NO and HNO within mitochondria, and suggests that H S may be the elusive thiol responsible for the reduction of nitrite. This study offers an answer to the decades-old question on the role of nitrite in the treatment of HS poisoning. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.